The lexical-semantical group of verbs of uncontrolled action in Ukrainian (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The analysis of lexical - semantical group of verbs of uncontrolled action is carried out in modern Ukrainian in the article; it is defined its semantic signs; paradigm and syntagmatical properties of verbs are described with sema «uncontrolled».
Keywords: lexical-semantical group; verb; action; value; uncontrolled; paradigma